Perancangan Aplikasi Belajar Shorof Krapyak Berbasi Android Dengan Metode Waterfall - Wava, Muhammad Vika; Prastowo, Wahit Desta; Ilyasir, Fiska; Pramuntadi , Andri (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Technology has progressed very rapidly in the last few decades, technology has an important role in modern learning because it provides access to resources and methods that are more effective and efficient. In the learning process of Shorof Krapyak, there are still some obstacles that are still faced. One of them is the conventional learning method. This method usually uses textbooks and lectures, as the main way to transfer knowledge to students. This method is considered less effective and interactive for students, thus causing students to feel bored and difficult to understand the material, by utilizing technological advances, one of which is by designing learning applications. That is the design of Shorof Krapyak learning application. By applying the Waterfall design method, and application testing methods using Blackbox Testing and Whitebox Testing. This application is systematically designed using Flutter Framework and Dart language. The results of this study with testing using Blackbox Testing and Whitebox Testing show that from the test scenarios that have been tested by producing a 100% success percentage rate. This shows that this application can run well, and optimally